2013
DOI: 10.4025/actasciagron.v35i4.16290
|View full text |Cite
|
Sign up to set email alerts
|

<b>Efficiency of the leaf disc method for estimating the leaf area index of soybean plants</b> - doi: 10.4025/actasciagron.v35i4.16290

Abstract: ABSTRACT. The objective of this study was to evaluate the efficiency of the leaf disc method for estimating the leaf area index (LAI) of soybean plants in comparison with the digital photo method. A split-plot experimental design was used with three replications. The LAIs calculated by the leaf disc and digital photo methods were compared at four growth stages in four soybean cultivars (subplot). These soybean cultivars were sowed in Guarapuava, Paraná State, Brazil, at three different sowing dates (main plot)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Lugg and Sinclair (1979) reported that soybean SLA increased until the R1 stage and then decreased steadily until mid-pod-fill (R5 to R6), but also varied among soybean cultivars. The SLA values calculated for soybean in this study are within the range reported in the literature (Junior and Kawakami 2013;Lugg and Sinclair 1979;Patterson and Flint 1983;Thompson et al 1995). Soybean did not compensate for interplant competition by altering its biomass partitioning or adjusting its SLA (i.e., leaf thickness), indicating that these are not ways in which soybean adjusts for interplant competition for light.…”
Section: Specific Leaf Areasupporting
confidence: 78%
“…Lugg and Sinclair (1979) reported that soybean SLA increased until the R1 stage and then decreased steadily until mid-pod-fill (R5 to R6), but also varied among soybean cultivars. The SLA values calculated for soybean in this study are within the range reported in the literature (Junior and Kawakami 2013;Lugg and Sinclair 1979;Patterson and Flint 1983;Thompson et al 1995). Soybean did not compensate for interplant competition by altering its biomass partitioning or adjusting its SLA (i.e., leaf thickness), indicating that these are not ways in which soybean adjusts for interplant competition for light.…”
Section: Specific Leaf Areasupporting
confidence: 78%
“…Plants were harvested and randomly chosen from each sub-plot to assess wheat yield measurements by measuring the LAI by using the disc method [ 45 ] the number of grains/spike and grain weight/spike (g) by taking the average of 10 random spikes from each plot; the number of spikes m −2 by counting the spikes in a random square meter in each plot; grain yield (ton ha −1 ) by weighing the grains threshed from the plot and calculating the yield for hectare; straw yield (ton ha −1 ) as the difference between biological yield and grain yield; biological yield (ton ha −1 ) by weighing all the plants from the harvested plot; 1000 grain wt. (gm); and the harvest index (HI) by dividing the grain yield by the biological yield.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the leaf discs were dried in a laboratory tray dryer at 70 C for 48 h. Once the discs were dried, each leaf disc was weighed again to obtain its dry mass. We used the obtained values of fresh and dry mass to calculate LWC as the proportion of the disparity between leaf fresh mass and dry mass to leaf dry mass, and SLA as the ratio between leaf area and leaf dry mass (Pierozan Junior & Kawakami, 2013). Species in resource-rich environments tend to have larger SLA (Cornelissen et al, 2003); thus, we categorized LWC and SLA as leaf resource acquisition traits.…”
Section: Leaf Mechanical and Secondary Metabolites Samplingmentioning
confidence: 99%